Sleep quality in opioid-naive and opioid-dependent patientson methadone maintenance therapy in Malaysia - Zahari, Z. (Scientific and Technical Research Council of Turkey, 2016)
Background/aim: Sleep disturbances may contribute to poor treatment outcomes in opioid-dependent patients. The extent to which the sleep profiles of opioid-dependent patients differ from those of the general Malaysian population is not documented. This study compared opioid-naive subjects and opioid-dependent patients on methadone maintenance therapy (MMT) in terms of their sleep quality. Materials and methods: Participants comprised Malay male opioid-naive subjects (n = 159) and opioid-dependent patients (n = 160) from MMT clinics in Kelantan, Malaysia, between March and October 2013. Sleep quality was evaluated using the translated and validated Malay version of the Pittsburgh Sleep Quality Index (PSQI). Results: The opioid-dependent patients exhibited higher global PSQI scores [adjusted mean (95% CI) = 5.46 (5.02, 5.90)] than the opioid-naive group [4.71 (4.26, 5.15)] [F (1, 313) = 4.77, P = 0.030]. Conclusion: This study confirmed the poorer sleep quality among opioid-dependent patients on MMT, as manifested by their higher global PSQI scores. The sleep complaints in this patient population are a factor to consider and, when necessary, sleep evaluation and treatment should be undertaken to improve MMT patients’ quality of sleep and overall treatment outcome.